A design method for improving assembly and environmental sustainability in packaging solutions: a case study in household appliances. Issue 4 (4th July 2021) - Postacchini, Leonardo; Cicconi, Paolo; Ciarapica, Filippo E.; Germani, Michele; Bevilacqua, Maurizio
ABSTRACT: By using a functional requirement analysis, through Design for Manufacture and Assembly and Design for Environment principles, this paper aims at showing a new design method to improve the overall assembly features and environmental sustainability of a packaging solution. This method provides to rank functional requirements according to three different design specifications and also to the number of relationships they have with each other. At the same time, a ranked order of importance for the packaging parts has been realised, considering the number of performed functions. The purpose of this method is to support the designers in focusing their attention on the most important packaging parts and, at the same time, giving them a clear idea of which are the most important functional requirements to be satisfied. This study has been focused on domestic household packaging, but the provided method can be extended to any particular packaging solution and its findings are still valid. According to the Design for Environmental perspective, the actual and the new resulting packaging solutions have been then compared through Life Cycle Assessment method. The results have shown the new packaging solution being able to cut down the environmental impacts, on average, of approximately 30%.